Management of alliance networks : formation, functionality, and post operational strategies - Sroka, Włodzimierz (SpringerBriefs in Business, 2013)
Effective management is crucial to the success of the inter-firm cooperation, and may reduce the risk that is inherently associated with these strategies. If cooperative strategy is to be successful, managers must have knowledge of factors that should be taken into consideration during formation and management of alliance networks. Therefore the main goal of this book is an understandable and simple presentation of the complexity involved in the management of alliance networks at three basic stages: formation stage, functioning stage, and post-operational stage. The book consists of six chapters, both theoretical and practical. A new model for management of alliance networks, which utilizes different instruments and tools, has been developed in the work. The last part of the book concentrates on the management of alliance networks in a practice-based framework based on the example of an engineering company which has formed a portfolio of bilateral alliances.